Smash Training Model in Badminton Game in College Students of the Faculty of Sports Science, Makassar State University - Muhammad Ishak; Moch. Asmawi; James Tangkudung; Firmasyah Dlis; Sahabuddin (International Journal of Science and Society, 2022)
In general, the purpose of this research and development is to produce a model of smash practice in badminton games for beginners. In addition, this research and development are carried out to obtain in-depth information about the competencies, characteristics, and initial abilities of FIK UNM students in the implementation of lectures, especially in Badminton Learning materials. The design in the research and development of this learning model uses the research and development model approach (Research & Development) from Brog and Gall. While the subjects in this research and development are all students of the Faculty of Sports Science, Makassar State University, which numbers 40 people. The instruments used in this research and development are questionnaires and questionnaires used to collect data at the stage of (1) needs analysis; (2) expert evaluation (initial product evaluation); (3) limited trials (small group trials); and (4) field testing. For the effectiveness test, the model used the badminton smash test and the rubric for assessing the correctness of the smash movement. To see the results of the effectiveness of the model, a statistical test was used using the test-test formula with a signification level of α = 0.05. Based on the development results, it can be concluded that: (1) The smash practice model in the badminton game for beginners can be developed and applied in training, and (2) The smash practice model in the badminton game for beginners has been developed, obtained data on the effectiveness and results of the development of the smash practice model in badminton games for beginners as well as can and deserve to be used in badminton training.